Care needs of the elderly who live alone: an intersectoral perception - Cardoso, Giovana Peres; Damaceno, Daniela Garcia; Alarcon, Miriam Fernanda Sanches; Marin, Maria Jose Sanches (Univ Federal Ceara, Dept Enfermagem, 2020)
Objective: to understand the perception of health and law professionals regarding care for frail elderly people who live alone. Methods: qualitative research, carried out through interviews with health and law professionals, using a vignette as a trigger, presenting the description of the story of a frail elderly woman who lived alone. Data were submitted to the thematic analysis technique. Results: the 23 professionals pointed out that the family members should be the responsible ones for the elderly; that institutionalization should take place as the last option; stressed the importance of multi-professional and intersectoral work; and recognized the limitations of the state. The professionals reported the appropriate interventions for the case. Conclusion: in care for the elderly who live alone, there are limitations for families, social care, and health services for the elderly, as well as the State, with the need to strengthen legally guaranteed resources.
Keywords: Frail Elderly; Intersectoral Collaboration; Patient Care Team; Aged Rights; Aging